Analisis Faktor-Faktor yang Mempengaruhi Live Streaming dan Affiliate Marketing terhadap Implusif Buying - Sinurat, Wanti; Salqaura, Siti Alhamra (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the factors influencing impulsive buying behavior among TikTok Shop users, particularly through the features of live streaming and affiliate marketing shopping. The research employs a quantitative approach using a survey questionnaire distributed to 100 TikTok Shop users in Medan who have previously made impulsive purchases. Data analysis includes validity and reliability tests, classical assumption tests, and multiple linear regression analysis to examine the effects of live streaming and affiliate marketing on impulsive buying. The results indicate that live streaming has a positive and significant effect on impulsive buying behavior. Real-time interaction, limited-time promotions, and interactive shopping experiences during live streaming sessions encourage consumers to make spontaneous purchases. Furthermore, affiliate marketing shopping also significantly influences impulsive buying, especially through engaging video content and influencer credibility. The credibility of sellers or affiliates is a crucial factor in building trust and driving unplanned purchase decisions. This study contributes to the development of digital marketing strategies, particularly on the TikTok Shop platform, by emphasizing the importance of optimizing live streaming and affiliate marketing features to stimulate impulsive buying behavior. The findings are expected to serve as a reference for business practitioners and researchers in understanding consumer behavior dynamics in the social e-commerce era.